Is there competition between Haemonchus contortus and Haemonchus placei in a pasture grazed by only sheep? - dos Santos, Michelle C. [UNESP]; Amarante, Mônica R.V. [UNESP]; Amarante, Alessandro F.T. [UNESP] (Elsevier, 2020)
This study aimed to evaluate the dynamics of Haemonchus contortus and Haemonchus placei infections and hybridization between these species in grazing sheep without contact with cattle. On January 14, 2014, sixteen young sheep were infected with 4000 infective H. placei third-stage larvae L3; 11 days later, another group n = 16 was infected with 4000 H. contortus L3. The establishment rates of H. contortus and H. placei L3 were, on average, 61.6 % and 56.8 %, respectively, in the permanent sheep. After the establishment of patent infections, all permanent sheep were allocated together in the same clean pasture where they grazed for the next 12 months. Euthanasia of a sample of the permanent sheep was performed every three months: in May, August, November and February. Two weeks before the sheep were removed for euthanasia, 2 worm-free tracer sheep were introduced to the pasture to evaluate the larval population in the field. The tracer sheep grazed alongside the permanent sheep for 2 weeks. Then, they were housed indoors for 20 days; at the end of this period, they were euthanized. Parasites were recovered from the permanent and tracer sheep and identified using morphological and molecular techniques. A total of 432 worms (from permanent and tracer animals) were analyzed by PCR using species-specific primer pairs. Of these specimens, only two (0.46 %) male worms were identified as hybrids: one was recovered from a permanent animal euthanized in August and the other from a tracer sheep that grazed in May. The last detection of adult H. placei worms occurred in sheep euthanized in May (approximately 3.5 months after the beginning of the grazing period). The morphological evaluation of the L3 produced in fecal cultures showed that H. placei were progressively replaced by H. contortus populations starting in March. The last trace of H. placei L3 was found in August, when a small percentage (0.5 %) of infective larvae with H. placei morphology was identified in a fecal culture. In conclusion, hybridization between H. contortus and H. placei can occur in the field during coinfection. It was demonstrated that H. placei established successfully in artificially infected worm-free sheep; however, with concomitant natural reinfection with H. contortus, the H. placei population showed a rapid decrease and was eliminated within a few months in an environment without cattle.
Keywords: Cross-infection; Gastrointestinal nematodes; Grazing; Ovine; Specificity